Unveiling transport properties of Co2MnSi Heusler epitaxial thin films with ultra-low magnetic damping. (December 2021) - de Melo, C.; Guillemard, C.; Friedel, A.M.; Palin, V.; Rojas-Sánchez, J.C.; Petit-Watelot, S.; Andrieu, S.
Abstract: The family of Co-based Heusler compounds contains promising candidates for spintronic applications regarding their predicted Half-Metal-Magnetic nature, ultra-low magnetic damping coefficients, high curie temperatures and tunable electronic properties. Here we focused on the transport properties of Co2 MnSi thin films with thickness in the range of 4-44 nm exhibiting magnetic damping in the 10 -4 - 10 -3 range. The goals of this study are to examine the impact of the peculiar electronic band structure on the transport properties, to identify the temperature-dependent scattering process, and to extract robust conduction parameters to exploit this material in magnetoelectric devices. In order to undoubtedly correlate all results, the full study has been performed on the same series of samples. Scanning transmission electron microscopy experiments were performed to check the chemically-ordered L21 phase in our films, and also allowed us to identify misfit dislocations generated at the interface with the substrate. The variation of the resistivity with film thickness was measured at different temperatures. The results are examined under the Fuchs and Sondheimer model which allowed us to extract the electron mean free path in Co2 MnSi in the temperature range 5 – 300 K. Values for the residual resistivity, Debye temperature, and distance between the Fermi energy and the conduction band for minority spins were obtained from the fit of the resistivity versus temperatures curves. A negative AMR ratio was measured for all the samples which confirmed the Half-metallic nature of the Co2 MnSi films. The determination of the ordinary Hall coefficient alloys allowed us to extract the carrier concentration and carrier mobility and their dependency on the temperature. Finally, scaling of the anomalous Hall coefficient with the longitudinal resistivity was performed indicating that skew scattering is the dominant temperature-dependent scattering mechanism in our films. Graphical abstract: Image, graphical abstract